Pendampingan Pelaporan Pajak Menggunakan E- Filing - Yayuk Nurjanah; Pingky Dezar Zulkarnain; Suci Sri Utami Sutjipto; Shania Gracia (LPPM Institut Bisnis dan Informatika Kesatuan, 2020)
Ciawi Pratama Tax Service Office (KPP) is an office engaged in taxation for public services with the aim of obtaining revenue in conducting tax reporting activities. The DJPOnline system is an application system built on a web-based basis which was developed as a means where taxpayers can register and report their tax obligations online and can be accessed anywhere. This application is connected in real time with the tax information system that is already running at the Ciawi Pratama Tax Service Office. The purpose of the discussion is to find out tax reporting services andtax reporting procedures online using e-Filing. The purpose oftax reporting online using e-Filing is to assist taxpayers in reporting in real time and can be done anywhere without the need to go to the Tax Service Office.The results of the discussion show that the online tax reporting procedure uses e-Filing to help taxpayers to be able to report their taxes in real time and can be done anywhere without the need to go to the Tax Service Office, with a connected internet network and an active email in the DJPOnline account. . Keywords ; Procedure, Tax Reporting, e-Filing